Table of Content - -, (Journal of agricultural, environmental and veterinary sciences, 2023)
Table of Content:1. Indicators of Desertification and its Impact on the Degradation of Agricultural Lands: A study of the Geography of Gadaref StateDr. Salwa Hassan Ahmed Sulieman2. Estimating an almost ideal demand system for red meat consumption in Libya Throughout the Year 2021 (A Case Study of the Municipality of Hay Al-Andalus)Mrs. Najat Mustafa Aljazeri, Prof. Said Yousif Khairi, Prof. Ragab Emhemed Alwerfelli3. Impact of Cookware Types on Leaking Heavy Metals into Food based on pH Values, and their Potential Impact on the Health Status of a Saudi Sample using a Survey Study DesignDr. Waheeba Ahmed Al-Faki, Ruya Mohammed Al-Shabrami, Mudhi Abdullah Aba Al-Khail1, Hala Abdul-Aziz Al-Muzaini, Aroob Ahmed Al-Ghafis, Safyah Ahmed Al-Adl, Aljouharah Khaled Al-Aqeel, Mashael Ali Al-Batah4. Biological Control of Lesser Date Moth (Batrachedra. Amydraula/ mayrick) using the local parasitoid Goniozus omanensisMrs. Samia Juma Suliman Al-Naabi, Mrs. Najma Mahmood Somar Al-Zadgali, Dr. Rashid Saif Al-Shidi5. Effect of crossbreeding on some productive characteristics of laying hensLecturer \ Esraa Mobsher Tawfeq, Asst-Lecturer \ Haytham Mohammed Sabeeh, Asst-Lecturer \ Omar AbdulHameed Al-Kurjia6. Chemical, Bioactive and antioxidant properties of Alhydwan(Boerhavia elegana Choisy) Seeds- A reviewMrs. Afnan Othman Mohammed Albisher, Dr. Asmahan Azhari Ali Mohammed, Prof. Sahar H. S. Mohamed
Keywords: Journal of Agricultural, Environmental and Veterinary Sciences